Efficacy of a Mindfulness-Based Intervention in Ameliorating Inattentional Blindness Amongst Young Neurosurgeons: A Prospective, Controlled Pilot Study - Pandit, Anand S.; de Gouveia, Melissa; Horsfall, Hugo Layard; Reka, Arisa; Marcus, Hani J. (Frontiers in Surgery, 2022)
Background Human factors are increasingly being recognised as vital components of safe surgical care. One such human cognitive factor: inattention blindness (IB), describes the inability to perceive objects despite being visible, typically when one’s attention is focused on another task. This may contribute toward operative ‘never-events’ such as retained foreign objects and wrong-site surgery. Methods An 8-week, mindfulness-based intervention (MBI) programme, adapted for surgeons, was delivered virtually. Neurosurgical trainees and recent staff-appointees who completed the MBI were compared against a control group, matched in age, sex and grade. Attention and IB were tested using two operative videos. In each, participants were first instructed to focus on a specific part of the procedure and assessed (attention), then questioned on a separate but easily visible aspect within the operative field (inattention). If a participant were ‘inattentionally blind’ they would miss significant events occurring outside of their main focus. Median absolute error (MAE) scores were calculated for both attention and inattention. A generalised linear model was fitted for each, to determine the independent effect of mindfulness intervention on MAE. Results Thirteen neurosurgeons completed the mindfulness training (age, 30 years [range 27-35]; female:male, 5:8), compared to 15 neurosurgeons in the control group (age, 30 years [27-42]; female:male, 6:9). There were no significant demographic differences between groups. MBI participants demonstrated no significant differences on attention tasks as compared to controls (t=-1.50, p=0.14). For inattention tasks, neurosurgeons who completed the MBI had significantly less errors (t=-2.47, p=0.02), after adjusting for participant level and video differences versus controls. We found that both groups significantly improved their inattention error rate between videos (t=-11.37, p<0.0001). In spite of this, MBI participants still significantly outperformed controls in inattention MAE in the second video following post-hoc analysis (MWU=137.5, p=0.05). Discussion Neurosurgeons who underwent an eight-week MBI had significantly reduced inattention blindness errors as compared to controls, suggesting mindfulness as a potential tool to increase vigilance and prevent operative mistakes. Our findings cautiously support further mindfulness evaluation and the implementation of these techniques within the neurosurgical training curriculum.